MADRASAH HEADMASTER COMMUNICATION IN IMPROVING LEARNING QUALITY AT MADRASAH TSANAWIYAH NEGERI 2 MEDAN - Syafaruddin Syafaruddin; Nurika Khalila Daulay; Muhammad Syarif Harahap (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
The purpose of this study are: 1) To find out the programs delivered by Madrasah Heads to educators in improving the quality of learning at Madrasah Tsanawiyah Negeri 2 Medan, 2) To find out the communication between Madrasah Heads and with the Curriculum Representative in improving the quality of learning at Madrasah Tsanawiyah Negeri 2 Medan, 3) To find out the communication between Madrasah Principals and educators in improving the quality of learning at Madrasah Tsanawiyah Negeri 2 Medan. This is qualitative research by using a phenomenological approach. The research findings show that the Head of Madrasah does carry out communication with the teachers and staff of Madrasah leaders in improving the quality of learning at Madrasah Tsanawiyah Negeri 2 Medan. Whereas the form of communication carried out by the madrasa head with the educators and leadership staff through internal communication using two forms; first, the head of the madrasah carries out downward communication  that is the communication that comes from the madrasah’s head to the educators and leadership staff. Second, the headmaster also carries out upward communication, which is the communication that comes from the educators and leadership staff to the headmaster. Keywords: Head of Madrasa, Communication, Learning Quality Improvement